The Competence Development of Vocational High School Teachers Using The "ANAK SALA" Model - Sudarno, Sudarno; Suyanto, Suyanto; Wibowo, Udik Budi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
The purpose of this research is to develop the competence of vocational high school teachers in Karanganyar Regency, especially in the pedagogical competence, professional competence, personality competence, and social competence by using a development model named "ANAK SALA". This study uses the Research and Development method. The sample used was 50 vocational high school teachers. The data collection method used a questionnaire technique. The data that has been collected, then analyzed comprehensively using the mean difference test and descriptive-analysis. In conclusion, the competence development of vocational high school teachers in Karanganyar Regency, Central Java can effectively be carried out using the "ANAK SALA" model.